A comparative study of thermochemical characteristics of lignocellulosic biomasses. (December 2019) - Kumar, Mohit; Upadhyay, S.N.; Mishra, P.K.
Abstract: The proximate, ultimate, and compositional analyses of wheat straw (WS), rice straw (RS), rice husk (RH), banana trunk (BT), arhar stalk (AS), and sugar cane bagasse (SB) were carried out. The bulk density and CVs were also measured. The functional groups and crystalline nature of each biomass were determined using FTIR and XRD analyses and thermal degradation was carried out using a TGA/DTA unit. The volatile matter (VM) was found to be the highest in SB and the lowest in RH. The highest carbon content was observed in RS and the lowest in BT. Sugar cane bagasse (SB) showed the highest calorific value (CV) and BT the lowest. The alcoholic and phenolic groups, alkanes and alkenes and some aromatic molecules were present in all biomasses. The RH was highly crystalline and BT was more amorphous in nature. During thermal pyrolysis maximum weight loss was recorded within the temperature range of 200–500 °C in all cases. The reaction kinetics triplets-activation energy (E), pre-exponential factor (A), and order of reaction (n) were evaluated using the TGA data and multiple linear regression method. The activation energy was found to be the lowest for SB and the highest for BT. Graphical abstract: Unlabelled Image Highlights: Thermo-chemical characterization of six agro-biomasses TGA-DTG analysis of agro-biomasses Evaluation of kinetic parameters through multiple linear regression analysis Comparison of six agro-biomasses with various coal using van Krevelen plot